PERBANDINGAN KOEFISIEN HETEROSIS ANTARA KAMBING BOERAWA DAN SABURAI JANTAN PADA BOBOT SAPIH DI KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Muhammad Harowi; Sulastri ,; M. Dima Iqbal Hamdani (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
Heterosis is the difference between the average results descent crosses with the average results of the parent type. Productivity of Boerawa and Saburai goat can be improved through crossbreeding program to utilize heterosis effect. Increased productivity by heterosis occurs due to increased heterozygosity but homozygosity decline. This research aims to: 1) know weaning weight of male Boerawa and Saburai goat; 2) comparing the coefficient of heterosis between male Boerawa and Saburai goat on weaning weight. This research was conducted on 12th August—13th September 2015 at the farmer group of Pelita Karya 3, Mitra Usaha, and Handayani in Sumberejo District, Tanggamus regency. This research used survey method. The sampling is done by using purposive sampling. The number of samples each 30 individuals male Boerawa and Saburai. The data obtained by the secondary data from recording data belongs to a group of farmers that include the name of farmer group, breeder, goat breed, age of the parent during childbirth, birth weight, type of birth, sex, weaning age, and weaning weight.Data were analyzed using student’s t-test on the significantly level 5% or 1%. The results of this research are : (1) the average of birth weight, weaning weight, and weaning weight adjusted of male Boerawa are 3.02±0.20 kg, 16.77±0.51 kg, and 20.82±0.71 kg and male Saburai goat are 3.36±0.31 kg, 17.86±0.79 kg, and 21.45±0.55 kg. (2) heterosis coefficient of male Boerawa and Saburai goat highly significant (P˂0,01). The average of heterosis coefficient Saburai goat (2.35±1.55) is lower than Boerawa goat (6.19±1.98). (Keywords : Boerawa goat, Saburai goat, weaning weight, heterosis coefficient).